A CONCEPTUAL STUDY OF SHEETPITA, UDARD AND KOTHA W.S.R TO URTICARIA : A REVIEW - Sason, *Rajveer; Sharma, Anita (International Journal of Ayurveda and Pharma Research, 2016)
Urticaria is a type I hypersensitivity reaction which is manifested because of exposure to such allergens. Epidemiology of Urticaria is increasing now days due to Industrialization and Agriculture. Vata and Kapha are two â€œDoshasâ€, which are primarily disturbed in this disease. In the combination with Pitta they create redness, swelling and itching on the skin. Acute urticaria is associated with more diffuse swelling of lips, face and throat and is spread all over the body.Urticaria is a vascular reaction of the skin characterized by a sudden general eruption of pale Sign and Symptoms of Urticaria resembles with Koth, Udarda, Sheetapitta. Kotha is one of the symptom mentioned by our Acharyas when body exposed to Asatmyaj Ahara and Vihara. Eg. Contact with poisonous material and Sheeta vayu etc. Our Ancient Acharayas has mentioned several classical Ayurvedic formulations for the cure of urticaria. Ayurveda provides us with detailed information about toxins, their management and methods of purging these poisons out of the body. Ayurvedic herbo mineral preparations restores healthy skin and cure urticaria by establishing the equilibrium of Tridosha (Vata, Pitta, Kapha) and Sapt dhatus (body tissues). The present paper intends to highlight the Ayurvedic management in reducing sign-symptoms and recurrence of the disease.